Integrasi Pengujian Peraturan Perundang-undangan di Mahkamah Konstitusi terhadap KUHP Baru Tantangan Harmonisasi Norma Pidana Nasional - Sulistiawati, Sulistiawati; Santoso, Muh. Arbai; Bimantara, Adrian; Evita, Chandra; Riyadi, Agus; Permana, Adhe; Candra, Firman Adi (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The New Criminal Code (KUHP Baru), enacted on December 6, 2022, and effective as of January 2, 2026, represents a significant transformation in Indonesia's criminal justice system. Its implementation not only shifts the approach to criminal law from retributive to restorative, but also opens avenues for the integration of legal review by the Constitutional Court (MK) to ensure the harmonization of national criminal norms. This research aims to analyze the mechanisms of MK's integration of reviewing laws and Regional Regulations (Perda) against the New Criminal Code, and its implications for Article 2 of the New Criminal Code regarding living law and formal legality. Furthermore, this study aims to identify and evaluate the challenges of harmonizing national criminal norms in MK's decisions concerning specific cases such as demonstrations, embezzlement, and insult to state institutions after the implementation of the New Criminal Code since 2026. The research method employed is a normative legal approach with secondary data types, including laws and regulations, MK decisions, and related legal literature. The findings indicate that MK plays a crucial role in maintaining the consistency of national criminal law through the constitutional review of the New Criminal Code and its derivatives. However, challenges in harmonizing national criminal norms persist, particularly in the context of Article 2 of the New Criminal Code which recognizes living law and formal legality, as well as in the regulation of specific cases such as demonstrations, embezzlement, and insult to state institutions. This study recommends better coordination among MK, legislative, and executive bodies to avoid normative conflicts and ensure the fair and effective application of criminal law.